2020
DOI: 10.3389/fgene.2020.00513
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Conformational Traits in Dairy Cattle With DeepAPS: A Two-Step Deep Learning Automated Phenotyping and Segmentation Approach

Abstract: Assessing conformation features in an accurate and rapid manner remains a challenge in the dairy industry. While recent developments in computer vision has greatly improved automated background removal, these methods have not been fully translated to biological studies. Here, we present a composite method (DeepAPS) that combines two readily available algorithms in order to create a precise mask for an animal image. This method performs accurately when compared with manual classification of proportion of coat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…With the advent of phenomics, these traditional phenotypes can be collected automatically on a continuous basis on a massive number of animals, without the need to disturb them. For instance, weight can be accurately measured using 3D imaging [17], or conformation features can be measured from images [26]. These precision livestock farming devices record under normal production conditions of market animals, and not only on elite animals in nucleus farms.…”
Section: Traditional Phenotypes Revisitedmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of phenomics, these traditional phenotypes can be collected automatically on a continuous basis on a massive number of animals, without the need to disturb them. For instance, weight can be accurately measured using 3D imaging [17], or conformation features can be measured from images [26]. These precision livestock farming devices record under normal production conditions of market animals, and not only on elite animals in nucleus farms.…”
Section: Traditional Phenotypes Revisitedmentioning
confidence: 99%
“…to measure similarities between images should be adapted to livestock, and new metrics for videos should be implemented as they are required to compare animal behaviors. Automatic conformation measures [26] must be improved to be performed in vivo with minimal human intervention. A further challenge is to incorporate all this information into genome predictions.…”
Section: The Way Aheadmentioning
confidence: 99%
“…The authors concluded that by leveraging the information from the CVS it was possible to yield more accurate genetic parameters due to the higher volume of data. In another study, Nye et al (74) developed a web scraper and an image segmentation algorithm to extract images and information from breeding programs catalogs. The information retrieved was used in a subsequent step to predict genetic parameters related to coat pigmentation and conformation traits in dairy cattle.…”
Section: Perspectives Of Cvs For High-throughput Phenotypingmentioning
confidence: 99%
“…In beef cattle, heritability and genetic correlations were estimated using image analysis for carcass traits 11 . Also, genetic parameters for coat color and conformational traits have been estimated in dairy cattle using images from web catalogs 12 .…”
Section: Introductionmentioning
confidence: 99%